TRADE EXAMINATION OF MARKING COSMETIC PRODUCTS - SIRENKO, SVITLANA; TERNOVA, ALLA; VLASENKO, IRUNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Cosmetic products occupy a rather important place in modern consumption models. Cosmetics are an integral part of our lives. In Ukraine, as in the whole world, the problem of falsification of cosmetic products is extremely acute. According to the EU cosmetic regulation, toxic substances that cannot be used in the production of cosmetics include endocrine drugs that affect the work of the hormonal system, preservatives that must undergo a strict assessment of their impact on product safety. An effective method of detecting falsification of cosmetic products is their trade examination. The article examines the peculiarities of commodity examination of cosmetic products. It was noted that the main method of detecting falsification of cosmetic products is their trade examination. The requirements for information regarding the examination of cosmetic products are highlighted, the analysis of the main documents used in the commodity examination of cosmetic products is carried out. The researched quality of labeling of certain types of cosmetic products. When examining cosmetic products, it is necessary to adhere to a certain algorithm. After collecting the information, the accompanying documents are studied, i.e. documents that contain the necessary and sufficient information for the identification of the consignments of goods along the entire way of goods transportation. There are gross violations in some cosmetic products, for example, the manufacturer’s address is missing from the labeling of Korean-made facial gel peeling. Some manufacturers indicate additional information on the label. Identification of the quality of the labeling of cosmetic products is one of the important stages in the general algorithm of commodity examination, which allows determining the compliance of the cosmetic product with regulatory documents at the very first stage and subsequently saving money and time for conducting a more complex instrumental examination.